Data Security for School Service Top-Up Transactions Based on AES Combination Blockchain Technology - Fadlil, Abdul; Riadi, Imam; Nugrahantoro, Achmad (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2020)
The application of Blockchain technology has begun to be widely accommodated in industrial and business practitioner environments as a safeguard of transaction security so that now including the education sector, non-business institutions enjoy the use of this technology to support the learning process. Information on the protected Blockchain can be in the form of transactions, assets, identities, and other information packaged in digital form. Information is collected in the form of blocks that are interrelated by using the hash function as cryptographic encryption. This research uses Blockchain for online pocket money top-up transactions for students. The use of a centralized Blockchain is centralized to reduce server procurement costs, but to increase the security of transaction information, modification of each block series is carried out using the AES cryptographic approach . The results showed that the attack by inserting a Cross-Site Scripting (XSS) script if you want to know the value of the top-up transaction amount, you must be able to hack the cryptographic process. This is supported by chain validation testing to determine how many block changes have been changed.